Whose Streets? Anarchism, Technology and the Petromodern State. - Truscello, Michael; Gordon, Uri (Anarchist Studies, 2013)
An introduction is presented in which the editor discusses various reports within the issue on topics including the challenges faced by anarchists Ben Brucato in confronting with the resource scarcity scenario, the intellectual vocabulary of a movement, and the idealisation of the biases of artisan.